A model of sustainable rural development through creative tourism: CREATOUR project - Bakas, Fiona; Duxbury, Nancy (Anais Brasileiros de Estudos Turísticos, 2019)
Addressing the theme of how sustainable rural futures can be realized by considering 21st century realities, this paper presents a unique project on the future of rural economic development and social cohesion through the initiation of creative tourism products in rural areas and small cities. The promotion of crafts to fuel rural socio-economic development is gaining momentum and simultaneously a change towards what is known as ‘transformative tourism’ (Pritchard, Morgan, & Ateljevic, 2011) is observed, as tourists demand more immersive experiences. Craft movements in the urban space which also act as vehicles for social cohesion within cities where isolation is common, have been gaining in popularity for the last 10 years. Creative tourism, which differs from cultural tourism in terms of being an active transfer of the past into the present via local-visitor interaction, rather than a passive observation of the past (Richards & Marques, 2012), offers a novel rural development tool that this paper investigates. This paper focus on the CREATOUR project which investigates how rural organizations, tourists and rural communities interact and forge new alliances in the Portuguese context. This three-year project started in 2016 and now has 40 pilot projects, which are entrepreneurs or organizations who are incentivized to offer innovative creative tourism products within rural areas and small cities. In this article, the ways in which the CREATOUR project can act as a sustainable rural development tool are analysed in terms of the evolving creative tourism offers and the development frameworks that creative tourism offers can be placed within, suggesting that this research and application project can be a model for other countries and provides advice on how to practically achieve this. Whilst at a preliminary stage, this project will have a large amount of data from tourists (through questionnaires handed out by pilot projects), IdeaLabs (meetings of pilots and researchers for knowledge exchange), e-portfolios, a documentary and researcher site visits, which partly inform this paper and will come to inform future research.